Torn Consciousness: Ilya Selvinsky, Yan Satunovsky and Uncensored Literature as a Deconstruction of the Soviet ‘Covenant with History’ - Kukulin, Ilya (Wiener Slawistischer Almanach, 2025)
This article examines the correspondence between Yan Satunovsky and Ilya Selvinsky, a rare example of systematic and long-term contact between a representative of uncensored poetry and a major, established Soviet poet (though Selvinsky sometimes wrote ‘for the desk drawer’ works that were unacceptable to Soviet censorship). While Selvinsky responded generally favourably to Satunovsky’s children’s poems, he reviewed the latter’s adult poems (now considered classics of uncensored Russian-language literature) negatively and wrote that they demonstrated a “disintegrated consciousness” (literally: “torn consciousness”). This article clarifies the context and significance of this formulation, which was important to the polemical strategy of literary Constructivism, the movement that Selvinsky headed in the 1920s. Furthermore, the unexpected clash between Selvinsky and Satunovsky demonstrates the incompatibility of two versions of Soviet modernist poetry: teleological and anti-teleological. The former was fundamental to poetry that adhered to official aesthetic and political guidelines, the latter to uncensored poetry.